What Strategies Are Effective to Support Food Security in Slow‐Onset Disasters? A Mixed‐Method Systematic Review of the Literature - Hiep N. Le; Ernesta Sofija; Neil Harris; Reny Noviasty; Thu Nguyen; Hai Phung (Food and Energy Security)
ABSTRACT Having access to food is a human entitlement and one of the essential goals of the sustainable development agenda. Despite growing concern about the impact of slow‐onset disasters on food security, most interventions have primarily targeted sudden‐onset disasters. As such, there has been limited attention to understanding the effectiveness of adaptation strategies in safeguarding food security during disaster events. The aim of this research was to synthesize all existing evidence on the effectiveness of adaptation strategies in addressing food insecurity during gradual‐onset disasters. This study employs Hadley et al.'s food security framework to examine the effectiveness of existing adaptation strategies in mitigating food insecurity concerns during slow‐onset disasters. A mixed‐method systematic review was conducted using five electronic databases up to July 2023 and followed the guidelines regarding the convergent segregated approach to synthesize the findings. The review showed that most studies (94.1%) focused on drought, neglecting other slow‐onset disasters. The strategies mostly focused on ensuring the availability and accessibility of food while giving little attention to food utilization. Most food security components have somewhat identified their effectiveness, except for food safety, with no studies exploring it. Findings from the mixed‐methods approach also highlight the double‐edged effects of adaptation strategies and the notable absence of reliable intervention evidence using randomized controlled trials. It is crucial for future research to broaden the scope to include the less studied types of slow‐onset disasters. Emphasizing neglected and underutilized species, along with food safety aspects, might unveil novel approaches to boost food utilization in fluctuating climates. Given the heterogeneous nature of slow‐onset disaster impacts, it is important to explore these dynamic and context‐specific aspects of adaptation strategies in different conditions. Utilizing methods like randomized controlled trials in future research will enhance the evidence base.